BindWeb: A web server for ligand binding residue and pocket prediction from protein structures. (16th November 2022) - Xia, Ying; Xia, Chunqiu; Pan, Xiaoyong; Shen, Hong‐Bin
Abstract: Knowledge of protein–ligand interactions is beneficial for biological process analysis and drug design. Given the complexity of the interactions and the inadequacy of experimental data, accurate ligand binding residue and pocket prediction remains challenging. In this study, we introduce an easy‐to‐use web server BindWeb for ligand‐specific and ligand‐general binding residue and pocket prediction from protein structures. BindWeb integrates a graph neural network GraphBind with a hybrid convolutional neural network and bidirectional long short‐term memory network DELIA to identify binding residues. Furthermore, BindWeb clusters the predicted binding residues to binding pockets with mean shift clustering. The experimental results and case study demonstrate that BindWeb benefits from the complementarity of two base methods. BindWeb is freely available for academic use at http://www.csbio.sjtu.edu.cn/bioinf/BindWeb/ .